Identification of Peatland Fire Vulnerability in Bukit Tunggal Village, Jekan Raya District, Palangka Raya City - Fabian Saldeova Y; Yosha Permana (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Palangka Raya, which is predominantly built on peatland areas, has a high level of vulnerability to forest and land fires (karhutla). The decline in groundwater levels during the dry season makes peat highly flammable, particularly during the occurrence of El Niño. Major fire events in 2015 (±402,779 ha) and 2019 (±343,353 ha), along with 902 hotspot detections in 2019, indicate that fire hazards in this region are recurring and persistent. This study aims to identify the level of peatland fire vulnerability in Bukit Tunggal Subdistrict, Jekan Raya District. The research employs a descriptive qualitative approach using secondary data obtained from government reports, hotspot data, and official statements. The findings show that Bukit Tunggal has a high level of vulnerability due to the dominance of peatland, land-use changes, and limited adaptive capacity. Therefore, this study recommends the implementation of integrated mitigation strategies, particularly through peat water management and strengthening community participation, in order to reduce fire risks at the local level.